Peran Digitalisasi Pemasaran dalam Meningkatkan Daya Saing UMKM - Farid Irgie Priyadi; Muhamad Erwin (Nolsatu Publisher, 2026)
Technological advancements have encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt digital marketing strategies to enhance competitiveness. This study aims to analyze the role of marketing digitalization, particularly visual-based digital campaigns and influencer promotion, in improving the competitiveness of local MSMEs. The research employed a quantitative descriptive approach using an online questionnaire distributed to consumers who interacted with MSME digital promotions. The collected data were analyzed descriptively. The results indicate that digital campaigns significantly influence consumer purchase decisions, with 90% of respondents rating digital campaigns as effective to very effective. Furthermore, 100% of respondents stated that digital marketing had a positive impact on MSME development. These findings confirm that marketing digitalization plays a strategic role in strengthening MSME competitiveness in the digital era.